Back to basics: an exploration of relationship experiences in adults recovering from substance dependence - Govender, Cassandra P (My University, 2016)
Substance dependence is a global issue that is becoming significantly more problematic. This is due to the fact that it does not just have a devastating effect on the individual but results in profound spin-off effects, which impact society as a whole. Much research has been conducted within this area and contemporary research has seemed to focus on the link between attachment styles and substance abuse. Since its conception by John Bowlby, attachment theory has achieved an empirical authority that has contributed to its popularity in modern times. However, despite this renewed interest there still exists a gap in the literature around the role that relationships, throughout the lifespan, play in areas such as pathology and recovery. Consequently, this research embarked on an interpretive phenomenological exploration of the way relationships impact the lives of individuals suffering from substance dependence. Adults in recovery from substance dependence were individually interviewed about their experiences of their relationships during and after their years of abusing substances. Hermeneutical phenomenological analysis was used to analyse this data and it revealed a typical model of pathology where a negative childhood experience had cascading effects that culminated in the later dependence on substances. Participants all highlighted relationships with themselves or others as pivotal to either seeking substances or to going into recovery. These themes were then located within Bowlby’s (1976, 1980) developmental pathways framework in order to make sense of the progression of substance dependence along the lifespan as it manifested in these participants.
A research report submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Arts in Clinical Psychology. Johannesburg, 2016
Keywords: Substance abuse--Patients--Rehabilitation--South Africa; Substance abuse--Treatment--South Africa; Attachment behavior